Experimental-Based Scientific Approach toward the improvement of Science Process Skill and Scientific Attitudes of Grade X Student MAN Ende - Melkyanus Kaleka; Fara Dillah M Nur (Universitas Negeri Yogyakarta, 2018)
This study aimed to: 1) know the influence of the implementation of experimental-based scientific approach on physic learning toward the improvement of Science Process Skill of class X student of MAN Ende on even semester of academic year 2016/2017, 2) know the influence of the implementation of experimental-based scientific approach on physics learning toward the improvement of scientific attitude of class X student of MAN Ende on even semester of academic year 2016/2017. The research type is experimental research with the pre-experimental design and one-shot case study model. The population of the study was students of class X IPA MAN Ende which had the total of 136 students, and the sample of research was 30 students by purposive sampling technique. The data of the research sample is the score of science process skills and students' scientific attitude. T-test of one sample was used in data analysis.The research results showed that: 1) Implementation of experimental-based scientific approach on physics learning has effect to the improvement of students science process skills of class X student of MAN Ende on even semester of academic year 2016/2017, due to the normality test using chi-square test obtained χ2count (4.536) less than χ2table (7.814), and result of data analysis on hypothesis test is obtained t-count (2.702) greater than t_table (1.699). 2) Implementation of experimental-based scientific approach on physics learning has effect to the improvement of science attitude of class X student of MAN Ende on even semester of academic year 2016/2017, due to by χ2 count (4.503) less than χ2table (7.814) and t_count (8.031) greater than t_table (1.699) on α = 5%, dk = 29.